Implications of the Use of Fintech Payment on Consumptive Behavior - Rika Dwi Ayu Parmitasari; Idris Parakkasi; Sapsuha, Mubasysyyratul Ummah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
The development of digital technology, especially fintech payments, has significantly changed people's consumption behavior, especially among millennials and Gen-Z. This phenomenon is characterized by the increasing use of digital payment platforms such as e-wallets and mobile banking, which provide ease and convenience in transactions. The rapid growth of fintech payments can potentially affect the consumption patterns and financial management of the younger generation, so it is important to study it more deeply. This study aims to analyze the implications of the use of fintech payments on the consumptive behavior of the millennial and Gen-Z generations. The research method uses a qualitative approach with data collection techniques through the dissemination of questionnaires with the help of social media. The main findings revealed ease of use, usefulness, and external factors (social environment, technological innovation, and digital capabilities). Fintech payments have a dual impact on the consumptive behavior of millennials and Gen-Z. While this technology offers unprecedented convenience and efficiency, fintech payments also have the potential to encourage consumptive behavior. In the future, it is necessary to increase financial literacy and understanding of Islamic consumption principles, so that consumptive behavior can be overcome and controlled at reasonable and safe limits.